Comparative Analysis Study of Audit Quality in Indonesia and Global - Kumalawati, Lely; Wibawa, Koerniawan Dwi (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This study applies the Krippendorff method, which aims to analyze the characteristics, themes, and concepts of audit quality research conducted by Indonesian and global researchers. Background Problems: Audit quality is a measurement often used to assess auditor performance. Novelty: This study identified articles with the keyword "audit quality" obtained from the Garuda Ministry of Education and Culture portal as representatives of the Indonesian research group and International journals (Scopus & Science Direct) as representatives of the global group. Research Method: This study applies content analysis that traces articles about audit quality using Leximancer software (version 4.5). This study used 75 articles from the journal Scopus, 75 articles from Science Direct journals and 53 from the Garuda portal. Finding/Results: The results from this analysis indicate fundamental similarities in the two research clusters, in which audit tenure, fees, and independence influence the majority of audit quality. Differences in the Indonesian cluster research focus more on the concept of assessment, pressure, and level of complexity. In contrast, the global research group mainly influences audit quality by turnover, capacity, and impact. Conclusion: Similar determinants in Indonesia and globally are independence, cost, and tenure, although the percentage of relevance and prominence is different. The difference between audit quality in Indonesia and audit quality globally is that audit quality in Indonesia focuses more on the concepts of judgement, pressure, and level of complexity. In contrast, turnover, capacity, and impact influence audit quality globally